Physiological Response and Aflatoxin Contamination in Maize (Zea Mays L.) Grown Under Varying Water-Deficit Levels in a Semi-Arid Region: Physiological Response and Aflatoxin Contamination in Maize - Hassan, Halgoord; Muhammed, Aram Abbas (Journal of Tropical Life Science, 2023)
The present study explored the effects of water deficit levels at different growth stages of maize (Zea mays L.) cultivated in semi-arid conditions with regard to physiological responses and aflatoxin contamination. The physiological growth changes of maize hybrids were gauged for parameters viz. relative water content (RWC, %), root-shoot ratio (R/S), and specific leaf area (SLA). At the same time, the study used HELICA total Aflatoxin Assay for estimating aflatoxin contamination in the produced maize kernel. Results revealed the third level of water-deficit, which extended to the dent stage, led to lower RWC%, and higher (R/S), alongside lower (SLA). Although the aflatoxin level was estimated to be 18.5 ppb in the maize kernels (FDA limit = 20 ppb), it was apparent that cultivation in a semi-arid condition runs the risk of aflatoxin contamination, likely due to water shortage and high growing temperatures.